Types and mode of formation of duricrusts - 309912 Kuhan Bala Subramaniam (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006